2018
DOI: 10.2351/1.5040624
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and possible estimation of keyhole depths evolution, using laser operating parameters and material properties

Abstract: The authors propose an analysis of the effect of various operating parameters on the keyhole depth during laser welding. The authors have developed a model that uses the analysis of the thermal field obtained in 2D geometry, which is mainly defined by the characteristic Peclet number. This allows us to show that the dependence of the aspect ratio R of the keyhole with the operating parameters of the process is a function of two parameters: a normalized aspect ratio R 0 , controlled by the incident laser power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 19 publications
(22 reference statements)
4
44
0
Order By: Relevance
“…After a few such small protrusions, the keyhole changes from a J-like shape to a reverse-triangle-like shape. The formation of small protrusions and the J-shaped keyhole have been discussed previously by other researchers [25], whereas the keyhole morphology change to the reversetriangle-like shape is a highly transient process, which is first observed here using a MHz x-ray imaging technique.…”
Section: Four Common Events In Laser-induced Spatteringsupporting
confidence: 67%
See 1 more Smart Citation
“…After a few such small protrusions, the keyhole changes from a J-like shape to a reverse-triangle-like shape. The formation of small protrusions and the J-shaped keyhole have been discussed previously by other researchers [25], whereas the keyhole morphology change to the reversetriangle-like shape is a highly transient process, which is first observed here using a MHz x-ray imaging technique.…”
Section: Four Common Events In Laser-induced Spatteringsupporting
confidence: 67%
“…As illustrated in Fig. 3(a), the front keyhole wall develops a slope under the scanning laser conditions [25]. The vapor plume is ejected in a primary direction normal to the inclined front keyhole wall towards the opposite direction of the scanning.…”
Section: Motion Tracking and Pressure-field Analysismentioning
confidence: 95%
“…Power and speed were chosen so that the ratio power/speed remains constant, in order to theoretically keep the same Volumetric Energy Density (VED), which is ratio of the laser power divided by the scanning speed times the laser spot area, as described by Gunenthiram et al (2018). Such an analytical formulation was used instead of other ones (using for instance powder bed layer or hatch distance as influent parameters) for the following reasons: (1) recent work by Fabbro et al (2018) have shown a linear dependence between fusion depth and such a VED formulation, (2) our experimental results on 316L exhibit a clear dependence between porosity rate (densification level) and such a VED, (3) it provides a physically realistic formulation of laser absorption which occurs mainly at the surface of the melt-pool and is not affected by powder thickness. As indicated by Scipioni Bertoli et al (2017), the use of VED as a mean for combining the power, speed and beam diameter process parameters in a single energy input is mostly efficient at low energy inputs, typically below 100 J/mm 3 .…”
Section: Materials and Sample Fabrication Methodsmentioning
confidence: 99%
“…We recall here the model that allows determining the dependence of the KH depth in the case of keyholes with rather large aspect ratios R = e/d where e is defined as the KH depth and d is the spot diameter [16]. For this regime, one considers that the KH is a vertical cylinder with a diameter d given by the spot diameter, whose wall is at a uniform evaporation temperature T v , which is moving with a welding speed V w inside a material at initial temperature T 0 .…”
Section: Model For Deep Penetration Regimementioning
confidence: 99%
“…In order to estimate these depths, many semi-analytical [3][4][5][6][7][8] or numerical [9][10][11][12][13][14][15] approaches have been considered. We had also recently proposed a relatively efficient and simple model [16] for estimating these KH depths based on a purely thermal analysis of the mechanisms involved, which makes it possible 2 of 22 to reproduce quite satisfactorily the experimental results of this "macro-welding" regime, obtained with various operating parameters and on materials with very different thermo-physical properties.…”
Section: Introductionmentioning
confidence: 99%